Do Big Five Personality Traits Moderate the Effects of Stressful Life Events on Health Trajectories? Evidence From the Health and Retirement Study. (1st June 2020) - Mitchell, Lauren L; Zmora, Rachel; Finlay, Jessica M; Jutkowitz, Eric; Gaugler, Joseph E
Abstract: Objectives: Theory suggests that individuals with higher neuroticism have more severe negative reactions to stress, though empirical work examining the interaction between neuroticism and stressors has yielded mixed results. The present study investigated whether neuroticism and other Big Five traits moderated the effects of recent stressful life events on older adults' health outcomes. Method: Data were drawn from the subset of Health and Retirement Study participants who completed a Big Five personality measure ( N = 14, 418). We used latent growth curve models to estimate trajectories of change in depressive symptoms, self-rated physical health, and C-reactive protein levels over the course of 10 years (up to six waves). We included Big Five traits and stressful life events as covariates to test their effects on each of these three health outcomes. We examined stressful life events within domains of family, work/finances, home, and health, as well as a total count across all event types. Results: Big Five traits and stressful life events were independently related to depressive symptoms and self-rated health. There were no significant interactions between Big Five traits and stressful life events. C-reactive protein levels were unrelated to Big Five traits and stressful life events. Discussion: Findings suggest that personality and stressful life events are important predictors of health outcomes. However, we found little evidence that personality moderates the effect of major stressful events across a 2-year time frame. Any heightened reactivity related to high neuroticism may be time-limited to the months immediately after a major stressful event.